Vibration Protection of Sensitive Components of Infrared Equipment in Harsh Environments - A.M. Veprik; V.I. Babitsky; N. Pundak; S.V. Riabzev (Shock and Vibration, 2001)
This article addresses the principles of optimal vibration protection of the internal sensitive components of infrared equipment from harsh environmental vibration. The authors have developed an approach to the design of external vibration isolators with properties to minimise the vibration-induced line-of-sight jitter which is caused by the relative deflection of the infrared sensor and the optic system, subject to strict constraints on the allowable sway space of the entire electro-optic package. In this approach, the package itself is used as the first-level vibration isolation stage relative to the internal highly responsive components.